KETIKA TANDA TIDAK LAGI PUNYA “PENGIRIM”: MENUJU SEMIOTIKA OTONOM - Hamdan, Faisal (SEMIOTIKA: Jurnal Komunikasi, 2025)
This article proposes a conceptual framework called Autonomous Semiotics to explain how signs operate and acquire meaning in digital ecosystems governed by algorithmic automation and artificial intelligence. The study departs from the limitations of classical semiotics, which assumes meaning production always comes from human intentionality. In contrast, within contemporary digital platforms, signs circulate, accumulate resonance, and shape interpretation without an identifiable human sender. Algorithmic systems—rather than communicators—regulate visibility, priority, replication, and distribution of signs. Theoretically, this study seeks to reformulate the foundation of communication studies by situating sign production within a non-human, computational mechanism. The article concludes that communication in the digital era can no longer be understood solely as a process of message exchange between sender and receiver, but as the operational agency of signs embedded in platform logic and automated systems.